2015
DOI: 10.1007/s11657-015-0215-6
|View full text |Cite
|
Sign up to set email alerts
|

Carpal and scaphoid fracture incidence in south-eastern Australia: an epidemiologic study

Abstract: Almost all fractures were the result of a fall. In males, carpal fractures were sustained mainly during early adulthood and in females during adolescence and after menopause. Incidence rates for males were higher than those in females for both scaphoid and non-scaphoid fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 19 publications
4
15
0
2
Order By: Relevance
“…The high ratio has been explained by male predominance and the physical demands placed on military personnel. Nonetheless, despite substantially lower overall fracture rates (32/100 000) others have demonstrated similar peak fracture incidences for young males, 153/100 000 [27].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…The high ratio has been explained by male predominance and the physical demands placed on military personnel. Nonetheless, despite substantially lower overall fracture rates (32/100 000) others have demonstrated similar peak fracture incidences for young males, 153/100 000 [27].…”
Section: Discussionmentioning
confidence: 94%
“…Previous epidemiological studies have identified very few elderly people with scaphoid fracture [5,19]. However, it has previously been reported that females have a young as well as old age peak incidence [19,27]. In a recent register study, the scaphoid fracture incidence was approximately 15/100 000 for people above 70 years of age [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations